2013
DOI: 10.2753/atp1084-1806350204
|View full text |Cite
|
Sign up to set email alerts
|

Social Enterprise and Dis/identification

Abstract: Social enterprise has been criticized for discursively transforming third sector organizations and practitioners into economic agents. Such a critique too readily construes the discourse of social enterprise as a deterministic force that encroaches on all aspects of organizational and individual identity. We reintroduce a sense of agency to discursive conceptualizations through an empirical study focusing on whether and how social enterprise infiltrates the third sector at the level of the subject. Drawing fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 49 publications
3
42
0
2
Order By: Relevance
“…While the research underpinning this paper was not aimed at studying discourse per se, the themes emerging through our qualitative research stood in contrast to the optimistic messages emanating from governmental reports. This partly reflects practitioners' agency (Dey and Teasdale 2013) in implementing social enterprise according to their social realities rather than policymakers' claims. This also resonates with the work of Howorth et al (2011) in England who found that the policy drive leads to a diverse application of the policy discourse in social enterprise.…”
Section: Reflections: Misconception Of Need?mentioning
confidence: 99%
See 1 more Smart Citation
“…While the research underpinning this paper was not aimed at studying discourse per se, the themes emerging through our qualitative research stood in contrast to the optimistic messages emanating from governmental reports. This partly reflects practitioners' agency (Dey and Teasdale 2013) in implementing social enterprise according to their social realities rather than policymakers' claims. This also resonates with the work of Howorth et al (2011) in England who found that the policy drive leads to a diverse application of the policy discourse in social enterprise.…”
Section: Reflections: Misconception Of Need?mentioning
confidence: 99%
“…For some, the political interest in, and the case for, social enterprise is premised upon the conviction that traditional Western models of welfare provision are coming to an end (Peredo 2011), and that welfare states are unaffordable (Roper and Cheney 2005), bureaucratic and inefficient, and so unable to meet the social needs of citizens (Dees 1998). This functionalist and managerial account (Dey and Teasdale 2013) considers social enterprise inevitable, and public policy as the means through which the Third Sector can be transformed into a more efficient mechanism of addressing social needs. In policy terms, as noted by Hudson (2009) and Amin (2009), it is recognised and accepted that a 'third system' (Pearce 2003) should exist in parallel to state and market, sometimes overlapping with the mainstream economy through its market orientation (for example, consumer cooperative organisations) or through the absorption of state welfare functions (as the case with social cooperatives in Italy) (Amin 2009, p. 33).…”
Section: The Role Of Social Enterprise In Contemporary (Liberal) Welfmentioning
confidence: 99%
“…Este cambio en el enfoque ha provocado que organizaciones sin fines de lucro adopten diferentes mecanismos de mercado que les provean de los medios necesarios para llevar a cabo su misión social (Dey & Teasdale, 2013).…”
Section: Introductionunclassified
“…Dey and Teasdale's (2013) article has its roots in the Social Enterprise School and deals with the manner in which social entrepreneurial organizations relate to, and are possibly influenced by, the discourse on social enterprises in the UK. This British study shows that the discourse did not affect the fifteen organizations included in the study to the extent the researchers had first predicted.…”
Section: Through Interviews With Homeless and Disadvantaged Members Omentioning
confidence: 99%
“…For example, the general manager of one sports club took an active stance against the discourse based on ideological reasons; the manager had severe doubts concerning the motives behind the British government's promotion of social enterprises. The government's main objective, according to the manager, was to facilitate cutbacks in the public sector rather than institute any societal improvements (Dey & Teasdale, 2013).…”
Section: Through Interviews With Homeless and Disadvantaged Members Omentioning
confidence: 99%